2010
DOI: 10.1021/am100293r
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Free-Standing, Electrochemically Active, and Biocompatible Graphene Oxide−Polyaniline and Graphene−Polyaniline Hybrid Papers

Abstract: In this work, we report a low-cost technique via simple rapid-mixture polymerization of aniline using graphene oxide (GO) and graphene papers as substrates, respectively, to fabricate free-standing, flexible GO-polyaniline (PANI) and graphene-PANI hybrid papers. The morphology and microstructure of the obtained papers were characterized by FESEM, FTIR, Raman, and XRD. As results, nanostructural PANI can be deposited on the surfaces of GO and graphene papers, forming thin, lightweight, and flexible paperlike hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
291
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 486 publications
(307 citation statements)
references
References 42 publications
15
291
0
1
Order By: Relevance
“…This is attributed to the good intrinsic biocompatibility and the hydrophilic nature of GO. Yan [123] obtained a similar conclusion when studying the biocompatibility of GO-polyaniline and graphene-polyaniline hybrid papers. Gurunathan [124] observed that microbially-reduced graphene oxide (M-rGO) exhibits significant biocompatibility for primary mouse embryonic fibroblast (PMEF) cells.…”
Section: Biological Property Of Go-based Materialssupporting
confidence: 55%
“…This is attributed to the good intrinsic biocompatibility and the hydrophilic nature of GO. Yan [123] obtained a similar conclusion when studying the biocompatibility of GO-polyaniline and graphene-polyaniline hybrid papers. Gurunathan [124] observed that microbially-reduced graphene oxide (M-rGO) exhibits significant biocompatibility for primary mouse embryonic fibroblast (PMEF) cells.…”
Section: Biological Property Of Go-based Materialssupporting
confidence: 55%
“…Although the Raman spectra of two textured graphene films also had both D and G bands at the similar positions, the intensity ratio of D/G increased obviously in comparison with that of the GO spectra. It agreed well with the graphene materials prepared by hydrazine reduction [22,23], indicating the realization of deoxygenation in electrochemically reduced graphene films. In addition, the result of electrical conductivity measurements showed that the electrical conductivity of the textured graphene films was approximately 15 S/cm, which was much larger than that of the textured GO films (< 10 7 S/cm).…”
Section: Resultssupporting
confidence: 83%
“…The PDMS mold was peeled off from the textured nickel layer, to form a freestanding nickel slice. GO was prepared from natural graphite [20][21][22] (See the Supporting Information for details). A homogeneous GO aqueous suspension (0.5 mg/mL) was obtained with the aid of sonication using a high-power (800 W) ultrasonic pole at 0°C for 1 h, and then the suspension was centrifuged at 3000 r/min for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Characterization of Graphene Quantum Dots GQD were synthesized following the modified method by Hummers where an orange yellow solution was obtained in photo-Fenton reaction of graphene oxide [59]. Graphene with 50 wt% KMnO 4 was successfully sheared as tiny dots by acidic suspension and the excess of KMnO 4 was consumed by hydrothermal process.…”
Section: Resultsmentioning
confidence: 99%